2017
DOI: 10.1051/0004-6361/201730859
|View full text |Cite
|
Sign up to set email alerts
|

A near-infrared interferometric survey of debris-disc stars

Abstract: We report the results of high-angular-resolution observations that search for exozodiacal light in a sample of main sequence stars and sub-giants. Using the "jouvence" of the fiber linked unit for optical recombination (JouFLU) at the center for high angular resolution astronomy (CHARA) telescope array, we have observed a total of 44 stars. Out of the 44 stars, 33 are new stars added to the initial, previously published survey of 42 stars performed at CHARA with the fiber linked unit for optical recombiation (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…It may indeed be possible that Altair's atmosphere is more metallic than its interior, as a possible consequence of a recent accretion of metals from a residual disc or planetoids. This idea is comforted by the fact that Nuñez et al (2017) found an extended, weak IR excess (a few % in K band) for Altair, which suggests the presence of a tenuous circumstellar material (possibly from a debris disc) within a few AU of the star.…”
Section: Massmentioning
confidence: 99%
“…It may indeed be possible that Altair's atmosphere is more metallic than its interior, as a possible consequence of a recent accretion of metals from a residual disc or planetoids. This idea is comforted by the fact that Nuñez et al (2017) found an extended, weak IR excess (a few % in K band) for Altair, which suggests the presence of a tenuous circumstellar material (possibly from a debris disc) within a few AU of the star.…”
Section: Massmentioning
confidence: 99%
“…In fact, this is the case for the zodiacal cloud, much of which is replenished from dust that originates from comets that disintegrate as they pass through the inner Solar System (Nesvorný et al 2010). Based on the NIR excess measured in nearby stars using interferometry, it has been estimated that ∼ 10 − 30% of AFGK-type stars have exozodi levels above 1% of the stellar flux (Absil et al 2013;Ertel et al 2014), with a tentative correlation with the existence of an outer reservoir of cold dust for FGK-type stars (Nuñez et al 2017). On the other hand, MIR excess are less commonly detected (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Interferometry is required to spatially resolve the thermal dust emission in the infrared and thus disentangle it from the host star. This has been done successfully for the hot dust using optical long baseline interferometry in the near-infrared (Absil et al 2006(Absil et al , 2013Defrère et al 2012b;Ertel et al 2014aErtel et al , 2016Nuñez et al 2017). In the mid infrared where HZ dust is the brightest, nulling interferometry (Bracewell & MacPhie 1979;Hinz et al 1998Hinz et al , 2000 has been used to suppress the bright, unresolved star light and detect the faint, extended dust emission (Stock et al 2010;Millan-Gabet et al 2011;Mennesson et al 2014;Ertel et al 2018b).…”
mentioning
confidence: 99%